Early effects of low benzene exposure on blood cell counts in Bulgarian petrochemical workers / Effetti ematologici dell’esposizione a basse dosi di benzene in lavoratori petrolchimici bulgari - Pesatori, A.C.; Garte, S.; Popov, et al., T. (La Medicina del Lavoro, 2009)
Objectives: Only few studies have examined early hematological effects in human populations exposed to low benzene levels and their findings are controversial. We evaluated hematological outcomes (WBC, neutrophils, lymphocytes, monocytes, eosinophils, basophils, RBC, Hb, HCT, MCV, platelets and MPV) in a population of 153 Bulgarian petrochemical workers exposed to benzene (range 0.01-23.9 ppm) and 50 unexposed subjects. Methods: Written informed consent was obtained and a self-administered questionnaire used to collect information on current smoking habits, lifestyle, and occupational activities. Exposure assessment was based on personal monitoring sampling the day before phlebotomy. Urinary trans-trans-muconic acid (t,t-MA) was determined at the beginning and end of the work shift. Based on individual airborne benzene measurements, study subjects were categorized in three exposure categories (referents, <1 and ≥1 ppm). Mean values of each hematologic outcomes in each exposure category were compared with the referent group using a multiple linear regression model adjusted for age, gender, current smoking habits and environmental toluene level. The influence of the CYP2E1 (RsaI and DraI) and NQO1 609C>T genetic polymorphisms on differential hematological parameters was also investigated. Results: No dose-response effect was observed for most of the examined hematological outcomes (WBC, lymphocytes, neutrophils, monocytes, RBC, Hb, HCT, MCV, platelets and MPV). The eosinophil count was inversely related to benzene exposure only among smokers. Conversely, basophils increased with increasing exposure. No effect on benzene hematotoxicity was found for any of the investigated polymorphisms. Conclusion: In our study we did not find a decline in WBC and lymphocytes related to benzene exposure. A myeloproliferative effect of benzene is highly unlikely to explain the observed reduction in eosinophils and increase in basophils as it would lead to a concordant depression in all granulocyte subpopulations. Whether benzene effects at low doses are present in Caucasian populations remains uncertain, thus warranting further investigations. Effetti ematologici dell’esposizione a basse dosi di benzene in lavoratori petrolchimici bulgari Solo pochi studi hanno analizzato le possibili conseguenze ematologiche dell’esposizione a basse dosi di benzene, con risultati contrastanti. Il nostro studio ha indagato parametri ematologici in una popolazione di 153 operai petrolchimici bulgari esposti a benzene e in 50 soggetti non esposti. Dopo raccolta di consenso informato e di dettagliate informazioni individuali attraverso questionario, l’esposizione a benzene è stata valutata mediante l’utilizzo di campionatori personali. L’acido trans-trans-muconico urinario è stato misurato all’inizio e alla fine del turno di lavoro e il giorno seguente ogni soggetto è stato sottoposto a prelievo venoso. In base all’esposizione individuale, i soggetti allo studio sono stati suddivisi in tre categorie (controlli, esposti a meno di 1 ppm, esposti a più di 1 ppm). Modelli di regressione multipla aggiustati per età, sesso, attuale abitudine al fumo e esposizione a toluene sono stati utilizzati per confrontare i valori ematologici in ciascuna delle tre categorie di esposizione. È stata anche valutata l’influenza dei polimorfismi nei geni metabolici CYP2E1 e NQO1 sui diversi parametri ematologici indagati. Per la maggior parte degli indicatori ematologici esaminati (leucociti totali, linfociti, neutrofili e monociti, globuli rossi, Hb, Ht, MCV, piastrine e MPV) non è emersa una relazione dose risposta con l’esposizione a benzene. Il numero di eosinofili è risultato inversamente correlato all’esposizione a benzene solo tra i fumatori, mentre il numero di basofili aumenta all’aumentare dell’esposizione. Tali effetti sono difficilmente attribuibili all’azione mieloproliferativa del benzene che più probabilmente porterebbe a una depressione di tutte le sottopopolazioni granulocitarie. Inoltre, non è emerso nessun effetto dei polimorfismi genetici sulle cellule ematiche. La nostra indagine non sembra evidenziare significativi effetti della esposizione a basse dosi di benzene sui parametri ematologici indagati.